Optimasi Suhu terhadap Pertumbuhan dan Kelulushidupan Ikan Heckel Discus (Symphysodon discus) - Triajiatma, Fiko; Julyantoro, Pande Gde Sasmita; Waskitasari, Alfi Hermawati (Current Trends in Aquatic Science; Vol 6 No 2 (2023), 2023)
This study aims to determine the optimization of temperature on the growth and survival of discus fish. The treatments used were different temperatures at 25°C, 28°C, and 31°C. Discus fish maintenance is carried out in 3 aquariums with a size of 120 × 40 × 40 cm which have been given a filter, aeration and heater. The water used is 120 liters, which has been aerated for 24 hours with a predetermined temperature using a heater (50W) and a water change of about 25% every week. Feeding is done by the satiation method, given 3 times a day with frozen worms where after 1 hour of feeding will be done to clean the remaining feed. Sampling of water quality (pH) using manual sampling method as a supporting parameter. The test fish used in this study were 5 cm discus fish. The number of fish used was 27 fish, and measurements were taken every 15 days with 3 repetitions. Length and weight growth of discus fish increased during the study. The growth of discus fish ( Symphysodon sp.) treated at 31°C was the most optimum growth with absolute length reaching 1,56 cm and absolute weight of 3,55 g compared to the 25°C and 28°C temperature treatments. The survival rate of discus fish in the 25° C, 28° C, and 31° C temperature treatments has a survival rate value of 100% and water quality that remains stable due to optimum temperature vulnerability.